Situating Martin Heidegger's claim to a "productive dialogue" with Marxism. Issue 4 (24th November 2017) - Griffiths, Dominic
Abstract : This critical review aims to more fully situate the claim Martin Heidegger makes in "Letter on Humanism" that a "productive dialogue" between his work and that of Karl Marx is possible. The prompt for this is Paul Laurence Hemming's recently published Heidegger and Marx: A Productive Dialogue over the Language of Humanism which omits to fully account for the historical situation which motivated Heidegger's seemingly positive endorsement of Marxism. This piece will show that there were significant external factors which influenced Heidegger's claim and that, when seen within his broader corpus, these particular comments in "Letter on Humanism" are evidently disingenuous, given that his general opinion of Marxism can only be described as vitriolic. Any attempt to explore how such a "productive dialogue" could be construed must fully contextualise Heidegger's claim for it. This piece will aim to do that, and more broadly explore Heidegger's general opinion of Marxism.